DESCRIPTION OF TECHNOLOGY FOR SEPARATION OF STARS FROM DIFFERENT VARIETIES OF RICE - Ishmukhamedova Rano Choriyevna; Matyakubova Karomat Shomurotovna; Reyimbayeva Munojot Anvar kizi (Research Parks Publishing LLC, 2021)
In recent years, not only around the world, but also in Uzbekistan, a large number of studies have been devoted to the isolation of starch from plant raw materials, which shows how quickly the demand for starch is growing all over the world. In addition to the traditional use of starch, for example, in the paper and cardboard industry, in recent years, a number of new directions for the effective use of starch and products from it have been expanding.